Identifying the Vulnerable to Poverty from Natural Disasters : The Case of Typhoons in the Philippines - Skoufias, Emmanuel; Kawasoe, Yasuhiro; Strobl, Eric; Acosta, Pablo (World Bank, Washington, DC, 2019)
This paper builds on the existing literature assessing retrospectively the quantitative effects of natural disasters on different dimensions of household welfare, to make progress toward the ex ante identification of households that are vulnerable to poverty due to natural disasters, especially typhoons. A wind field model for the Philippines is employed to estimate local wind speeds at any locality where a tropical typhoon directly passes over or nearby. The estimated wind speeds are merged with the household Family Income and Expenditure Surveys at the barangay level, and consumption expenditures are then regressed against wind speed (or a related damage index) and household socioeconomic characteristics. The estimated coefficients from the regression model are then used to estimate ex ante household vulnerability to poverty (the likelihood that household consumption falls below the poverty line) in the event of future natural disasters of different intensities.